Analisis Makna Frase “Lembu Jantan Kedua”: Studi Eksegese Hakim-Hakim 6:25-26 - Pattinaja, Aska Aprilano; Kiamani, Andris (Sekolah Tinggi Teologi Berita Hidup, 2025)
The book of Judges 6 is a book that tells the life of the Israelites during the time of the Judges, and one of the most famous stories is about the life of Gideon, an outstanding judge. In verses 25-26 there is an unusual line of narration, which readers will find odd, concerning the